2023
DOI: 10.1038/s43247-023-00757-x
|View full text |Cite
|
Sign up to set email alerts
|

Rising water-use efficiency in European grasslands is driven by increased primary production

Abstract: Water-use efficiency is the amount of carbon assimilated per water used by an ecosystem and a key indicator of ecosystem functioning, but its variability in response to climate change and droughts is not thoroughly understood. Here, we investigated trends, drought response and drivers of three water-use efficiency indices from 1995–2018 in Europe with remote sensing data that considered long-term environmental effects. We show that inherent water-use efficiency decreased by −4.2% in Central Europe, exhibiting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…While our study sheds light on the spatial variations of WUE and GPP, it is important to indicate the presence of additional influential factors. The complexity of interactions between climatic conditions, topography, and vital ecological factors contributes to the observed spatial heterogeneity of WUE and GPP [100,101].…”
Section: Spatia-temporal Variability Of Carbon-water Fluxes In the St...mentioning
confidence: 99%
“…While our study sheds light on the spatial variations of WUE and GPP, it is important to indicate the presence of additional influential factors. The complexity of interactions between climatic conditions, topography, and vital ecological factors contributes to the observed spatial heterogeneity of WUE and GPP [100,101].…”
Section: Spatia-temporal Variability Of Carbon-water Fluxes In the St...mentioning
confidence: 99%
“…The coupled product can effectively avoid internal inconsistencies between ET and GPP from the uncoupled product and therefore could provide higher-accuracy eWUE estimates [13]. Over the years, a large amount of eWUE-related research (e.g., the spatial and temporal variation of eWUE, the response of eWUE to drought and natural and human activities, and the driver of eWUE changes [1,[39][40][41][42][43][44][45][46][47][48]) has been conducted for various PFTs (including but not limited to cropland); however, most of these studies calculated eWUE based on the MODIS product, whose accuracy is strongly queried by this study as well as previous studies [2,13,49]. This study indicates that the coupled product is more suitable and effective to be applied in the eWUE-related research for different crop species to reduce the uncertainty from the inaccurate RS-based eWUE estimates from the uncoupled products.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…According to most studies, WUE has increased over the last 2 decades, which is partially explained by (1) an increase in GPP due to rising atmospheric CO 2 concentration, which results in a higher net carbon gain, with or without a reduction in stomatal conductance and reduced transpiration rates (Keenan et al, 2013), and/or (2) a reduction in stomatal conductance caused by water deficits (Saurer et al, 2004), which reduces transpiration to a greater extent than carbon assimilation. Nevertheless, other research has suggested that ecosystem WUE may decrease when climate warming (Boeck et al, 2006) or nitrogen deposition are considered (Huang et al, 2015), and this response may vary depending on the ecosystem type and hydroclimate (Terán et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A study that included all European ecosystems showed that WUE is more related to changes in GPP in drier ecosystems, whereas it is more related to changes in ET in more humid environments (Terán et al, 2023). As ET is determined by both E and T , partitioning of these would allow us to differentiate between biological (T ) and physical (E) drivers of evaporative losses (Paul-Limoges et al, 2020).…”
Section: Introductionmentioning
confidence: 99%